Diachronous primary Neuroendocrine tumour of the mediastinum: Dual FDG and DOTA avidity on PET/CT - Nadia Nazir; Ayesha Zubair; Aamna Hassan; Kashif Saddique (Journal of the Pakistan Medical Association, 2026)
Primary neuroendocrine tumours (NETs) of the mediastinum are exceedingly rare, accounting for a small fraction of thoracic neoplasms. Their biological behaviour is heterogeneous, ranging from indolent to highly aggressive depending upon their histological grading. Dual-tracer PET/CT imaging with fluorodeoxyglucose (FDG) and gallium-68 DOTA-conjugated peptides provides complementary information, reflecting heterogeneity of tumour including both metabolic activity and somatostatin receptor expression.